Rifaximin Improves Spatial Learning and Memory Impairment in Rats with Liver Damage-Associated Neuroinflammation - Paola Leone; Gergana Mincheva; Tiziano Balzano; Michele Malaguarnera; Vicente Felipo; Marta Llansola (Biomedicines, 2022)
Patients with non-alcoholic fatty liver disease (NAFLD) may show mild cognitive impairment. Neuroinflammation in the hippocampus mediates cognitive impairment in rat models of minimal hepatic encephalopathy (MHE). Treatment with rifaximin reverses cognitive impairment in a large proportion of cirrhotic patients with MHE. However, the underlying mechanisms remain unclear. The aims of this work were to assess if rats with mild liver damage, as a model of NAFLD, show neuroinflammation in the hippocampus and impaired cognitive function, if treatment with rifaximin reverses it, and to study the underlying mechanisms. Mild liver damage was induced with carbon-tetrachloride. Infiltration of immune cells, glial activation, and cytokine expression, as well as glutamate receptors expression in the hippocampus and cognitive function were assessed. We assessed the effects of daily treatment with rifaximin on the alterations showed by these rats. Rats with mild liver damage showed hippocampal neuroinflammation, reduced membrane expression of glutamate N-methyl-D-aspartate (NMDA) receptor subunits, and impaired spatial memory. Increased C-C Motif Chemokine Ligand 2 (CCL2), infiltration of monocytes, microglia activation, and increased tumor necrosis factor α (TNFα) were reversed by rifaximin, that normalized NMDA receptor expression and improved spatial memory. Thus, rifaximin reduces neuroinflammation and improves cognitive function in rats with mild liver damage, being a promising therapy for patients with NAFLD showing mild cognitive impairment.